Hepatoprotection and Phytochemistry of the Vietnamese Herbs Cleome chelidonii and Cleome viscosa Stems - Nhat Minh Phan; Thi Hong Tuoi Do; Le Thanh Tuyen Nguyen; Trong Tuan Nguyen; Quoc Luan Ngo; Trong Duc Tran; Quan Hien Nguyen; Bui Linh Chi Huynh; Diep Xuan Ky Nguyen; Trong Dat Bui; Dinh Tri Mai; Tan Phat Nguyen (Journal of Chemistry)
The study aims to determine the hepatoprotective effect of n-hexane, ethyl acetate, and methanol extracts of the leaves and stems of two Cleome species against carbon tetrachloride- (CCl4-) induced liver toxicity both in vitro using human hepatoma (HepG2) cells and in vivo in rats as well as the hepatoprotective property of all isolated compounds on HepG2. After 72 h of treatment, at the concentrations of 25, 50, and 100 μg/mL, the methanol of C. chelidonii stems (CCSM) ranged from 18.6% to 20.8%, whereas the methanol of C. chelidonii stems (CVSM) increased from 12.3% to 17.2% cell viability. The results show that CCSM and CVSM significantly expressed in vitro hepaprotective activity on HepG2. Therefore, the animals were daily treated with these extracts at the doses of 15, 30, and 45 mg/kg body weight for 5 days, and CCl4 was injected (2 ml/kg body weight, i.p.) on the 2nd and 3rd days. Levels of aspartate aminotransferase (ALT) and alanine aminotransferase (AST) in the blood were measured and compared to the silymarin control. The treatments with CCSM and CVSM (30, and 45 mg/kg) possessed significant hepatoprotection and were comparable with the activity of silymarin. Further, phytochemical studies of these ones were conducted and led to the identification of eight flavonoids: visconoside A (1), visconoside B (2), quercetin 3-O-β-D-glucopyranoside 7-O-α-L-rhamnopyranoside (3), kaempferol 3-O-β-D-glucopyranoside 7-O-α-L-rhamnopyranoside (4), cleomeside A (5), cleomeside B (6), cleomeside C (7), and quercetin-3-O-[β-D-glucopyranosyl-(1⟶2)]-α-L-rhamnopyranoside 7-O-α-L-rhamnopyranoside (8). Two major flavonoids (1 and 4) displayed significant hepatoprotective property (at the concentration of 100 μM, the prevention percentage values were 66.5% and 74.2%, respectively, compared to the quercetin control, with value of 80.3%).